LAZIZMU Philanthropy Potential in The Empowerment of Mustahiq’s Economic and Welfare (A Case Study in Probolinggo, Jember, and Pasuruan) - Benny Prasetiya; Heri Rifhan Halili; M. ALfi Syahrin; Muhammad Arifin (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2021)
Indonesia has a large zakat potential and has not been widely used for economic empowerment for the poor. Lazismu, as part of the national zakat institution, develops to provide solutions in zakat management in the form of economic empowerment for the poor to turn mustahiq into muzakki. This study was field research, and the data were obtained directly from the field and research objects. The research applied a normative sociological approach. This research was descriptive-analytic and clearly and in detail described the phenomena as the main problem without doing hypotheses or statistical calculations. Specifically, this research intended to describe in general the management of zakat conducted by Lazismu in Probolinggo, Jember and Pasuruan, then systematically reviewed them to achieve Lazismu’s Role strategy in poverty alleviation for the people of Probolinggo, Jember and Pasuruan, so that it was easier to understand and conclude. The results showed that the three Regional Lazismu in this study carried out the empowerment of mustahik to become muzakki with economic empowerment. Early empowerment is carried out by providing training and assistance to Mustahiq in managing productive economic businesses that are carried out sustainably. Economic empowerment for mustahiq has the potential to improve the economy to be more independent in running their business.